2005
DOI: 10.1007/s00248-005-0258-0
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Non-Legionella Bacteria on the Uptake and Intracellular Replication of Legionella pneumophila in Acanthamoeba castellanii and Naegleria lovaniensis

Abstract: In aquatic environments, Legionella pneumophila survives, in association with other bacteria, within biofilms by multiplying in free-living amoebae. The precise mechanisms underlying several aspects of the uptake and intracellular replication of L. pneumophila in amoebae, especially in the presence of other bacteria, remain unknown. In the present study, we examined the competitive effect of selected non-Legionella bacteria (Escherichia coli, Aeromonas hydrophila, Flavobacterium breve, and Pseudomonas aerugino… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
50
0
4

Year Published

2008
2008
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(57 citation statements)
references
References 23 publications
3
50
0
4
Order By: Relevance
“…L. pneumophila infects at least seven genera and 17 species of protozoa (28,67) and, therefore, it is reasonable to think that certain bacterial factors might have evolved to have greater importance in only certain protozoa. Previous studies have found that the growth and uptake of wild-type L. pneumophila can vary between Acanthamoeba, Hartmannella, and Naegleria hosts (24,38,55,71). But, few past studies have examined specific mutants of L. pneumophila for their capacity to infect multiple protozoa (55,77).…”
Section: Discussionmentioning
confidence: 99%
“…L. pneumophila infects at least seven genera and 17 species of protozoa (28,67) and, therefore, it is reasonable to think that certain bacterial factors might have evolved to have greater importance in only certain protozoa. Previous studies have found that the growth and uptake of wild-type L. pneumophila can vary between Acanthamoeba, Hartmannella, and Naegleria hosts (24,38,55,71). But, few past studies have examined specific mutants of L. pneumophila for their capacity to infect multiple protozoa (55,77).…”
Section: Discussionmentioning
confidence: 99%
“…To assess L. pneumophila growth within mammalian cells, we infected human U937 macrophages (ATCC CRL-1593.2) as previously done (7). To examine the ability of L. pneumophila strains to grow in protozoa, A. castellanii (ATCC 30234), H. vermiformis (ATCC 50237), and Naegleria lovaniensis (ATCC 30569) were infected as described previously (19,27,30,43,44). H. vermiformis and N. lovaniensis were infected in ATCC medium number 1034 that lacked its serum component, whereas infection of A. castellanii utilized protease peptone-yeast extract (PY) medium.…”
Section: Methodsmentioning
confidence: 99%
“…These results highlight Naegleria as a useful host for the replication and distribution of L. pneumophila (268). Bacterial attachment and uptake occurs through a receptor-mediated endocytosis, which requires de novo synthesis of host proteins.…”
Section: Host For Other Microbesmentioning
confidence: 85%